A highly selective and sensitive fluorescent chemosensor for detection of CN−, SO32− and Fe3+ based on aggregation-induced emission. Issue 2 (14th December 2015) - Yang, Xiaodong; Chen, Xiuli; Lu, Xiaodan; Yan, Chenggong; Xu, Yikai; Hang, Xiaodong; Qu, Jinqing; Liu, Ruiyuan
Abstract : An aggregation-induced emission based sensor that detects CN −, SO3 2− and Fe 3+ in aqueous solution and can be applied in test strips and cellular imaging was designed. Abstract : A novel fluorescence chemosensor1 with aggregation-induced emission was designed and synthesized through a nucleophilic addition reaction between cyanide and triphenylamine. It exhibited remarkable selectivity and high sensitivity and was able to detect Fe 3+, CN − and SO3 2− in almost pure aqueous solution with low detection limits of 1.44 μM, 9.88 nM and 0.107 μM, respectively. Job's plot and 1 H NMR data showed that the binding stoichiometry of1 with Fe 3+, CN − or SO3 2− was 1 : 1. Further observations of 1 H NMR titration suggested that a coordination bond was formed between two cyano of1 and Fe 3+ which resulted in fluorescence quenching of1 after detection of Fe 3+, whereas the nucleophilic addition of cyanide or sulfite to the vinyl group was responsible for the fluorescent quenching of CN − or SO3 2− toward1 . The biological applications of1 were also evaluated and it was found to exhibit low cytotoxicity and membrane permeability. In addition, 1 could also be made into test strips to detect Fe 3+ and CN − and was employed as a sensor for detection Fe 3+ in living cells.